Análise da compatibilidade de um estudo preliminar de arquitetura de construção de um edifício de pequeno porte (tiny house) com elementos da legislação urbana do município de Curitiba vigente em 2020 - Durce, Dario Correa (2021)
Tiny houses are not new, from a holistic point of view they have existed since the dawn of humanity. However, the term tiny house today is associated with an alternative model of middle class housing in english-speaking countries such as the USA and Australia, mainly due to the unsustainability of the traditional model of housing and based on pragmatism. This dissertation analyzes the compatibility of a preliminary architectural project for the construction of a tiny house with elements of the urban legislation of the municipality of Curitiba in force in 2020. The scientific method used is design science research. The artifact was designed by the author and validated using the Appendix Q of the International Residential Code. The analysis of the artifact was made based on Law n. 11.095/2004 (Posture Code) and in Ordinance n. 80/2013 of the municipality of Curitiba. The synthesis is that the design of a tiny house can comply with the international code and, at the same time, not comply with the urban legislation of the city of Curitiba, with the main impediments to its construction and implementation being the lack of definition and typification of the tiny house and its upper floor, which does not fit the definitions of mezzanine and attic, and the minimum and maximum ceiling heights of the compartments established by Ordinance n. 80 (Annex III). Curitiba’s urban legislation in force in 2020 is incompatible, totally or partially, with tiny houses designed according to the existing international code.